CREATING ARTIFICIAL SHOOTING STARS – A JAPANESE SCIENTIST’S DREAM COME TRUE - MPRC, Pusat Media & Perhubungan Awam (2017)
USM, PENANG, 22 February 2017 – ALE Co., Ltd is a technology company from Japan which has developed a technique of offering ondemand manmade ‘shooting stars’ for entertainment purposes, which could be seen on the ‘blank canvas’ of the night sky, hence the name “Sky Canvas”.